WALKING THE TIGHTROPE: BALANCING EMPATHY AND PROFESSIONALISM IN PSYCHIATRIC NURSING - Hassan, Fatima Abdelrahman (Research Journal of Health, Medicine and Nursing, 2024)
In the field of psychiatric nursing and psychotherapy, "limit setting" is a concept that plays a crucial role in guiding therapeutic relationships and patient treatment. Originally rooted in psychoanalytical theory, it was primarily aimed at establishing the boundaries of therapeutic relationships, thereby helping patients improve their selfperception. However, the concept of limit setting has evolved over time to encompass behavior modification and active patient engagement in the treatment process. Limit setting, in contemporary practice, is multifaceted. Firstly, it serves as a means to ensure patient safety by preventing them from engaging in potentially harmful behaviors, such as reacting violently to others. Simultaneously, it can be a valuable tool for fostering a sense of security and containment among patients. This is achieved by empowering them to recalibrate their behaviors in more socially acceptable and appropriate ways.